1T′‐Mo1−xWxS2/CdS Heterostructure Enabling Robust Photocatalytic Water Splitting: Unveiling the Interfacial Charge Polarization. Issue 6 (30th March 2018) - He, Qun; Wan, Yangyang; Zhang, Youkui; Jiang, Hongliang; Liu, Hengjie; Zheng, Xusheng; Chen, Shuangming; Wu, Xiaojun; Song, Li
Abstract : Transition metal dichalcogenides are generally considered as highly efficient and cost‐effective cocatalysts used in heterostructure‐based photocatalysis systems. The electronic structure of the transition metal dichalcogenide is considered as an important parameter that can influence the interfacial charge states of the heterostructure and thereby tune the catalytic performance. Thus, probing the interfacial charge states based on the understanding of the electronic structure is highly desirable to enhance the catalytic performance. Here, a model heterostructure comprising n‐type CdS and metallic 1T′‐Mo1− x W x S2 nanosheets is established. The interfacial charge states are comprehensively dissected by utilizing synchrotron‐based X‐ray absorption spectroscopy, photo‐electrochemistry characterization, and density functional theory calculations. As demonstrated, the formation of the Schottky junction leads to the increase of the electron density in the cocatalyst; thus, significantly enhanced catalytic performance is delivered. This survey provides deep insights into the interfacial charge states from the view of high‐efficiency photocatalysis systems design. Abstract : 1T′‐Mo1−x W x S2 /CdS heterostructure enables robust photocatalytic water splitting performance with a rate increase of 94.2‐fold compared to bare CdS. Meticulous and advanced synchrotron radiation‐based spectroscopic characterization and first‐principles theory calculations demonstrate that the interfacial charge polarization between 1T′‐Mo1− x W x S2 and n‐CdS endows the 1T′‐Mo1− x W x S2 with significantly enhanced hydrogen evolution ability.